2020
DOI: 10.1002/mop.32619
|View full text |Cite
|
Sign up to set email alerts
|

A compact flower slotted dual band notched ultrawideband antenna integrated with Ku band for ultrawideband, medical, direct broadcast service, and fixed satellite service applications

Abstract: A compact flower slotted antenna (FSA) for dual band eliminated ultrawideband (UWB) integrated with Ku band applications is proposed. The basic FSA with modified ground structure is utilized for obtaining fractional bandwidth of 137% (3.45-18.45 GHz). The dual band eliminated frequencies are achieved by a via hole to eliminate 5.39 to 5.90 GHz (upper WLAN band) frequencies and by utilizing symmetrical inverted L-shaped parasitic elements to notch 7.30 to 7.75 GHz (downlink of X-band satellite communication lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…For the intended dual band notched UWB radiator, the gain fluctuates from 2.94 dBi to 4.82 dBi with an average gain of 3.07 dBi and abruptly falls to −5.23 dBi and −8.25 dBi at notch frequencies of 3.3 and 5.33 GHz, respectively. The abrupt change of gain at 3.3 GHz and 5.33 GHz confirms that the proposed antenna effectively eliminates the interference [22] due to WiMAX and WLAN bands, respectively. Similarly, the abrupt changes in radiation efficiencies of 40.23% and 28.23% are noticed at 3.3 GHz and 5.33 GHz to notch WiMAX and WLAN bands, respectively, as shown in Figure 7(d).…”
Section: Resultsmentioning
confidence: 60%
“…For the intended dual band notched UWB radiator, the gain fluctuates from 2.94 dBi to 4.82 dBi with an average gain of 3.07 dBi and abruptly falls to −5.23 dBi and −8.25 dBi at notch frequencies of 3.3 and 5.33 GHz, respectively. The abrupt change of gain at 3.3 GHz and 5.33 GHz confirms that the proposed antenna effectively eliminates the interference [22] due to WiMAX and WLAN bands, respectively. Similarly, the abrupt changes in radiation efficiencies of 40.23% and 28.23% are noticed at 3.3 GHz and 5.33 GHz to notch WiMAX and WLAN bands, respectively, as shown in Figure 7(d).…”
Section: Resultsmentioning
confidence: 60%
“…The drawback of this kind of antenna is that omnidirectional emission leads to high interference and energy loss in unwanted directions, meaning that the main lobe of the radiation pattern is low. Moreover, the back lobe radiation is high and capable of affecting the surrounding environment changes [7][8][9][10][11][12]. Therefore, under these circumstances, the directional radiation is more favoured as it guarantees more sensible use of the radiated power, which can be explained through a deep analysis related to Effective Isotropic Radiated Power (EIRP) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Meena M. L. et al [15] reported a semi-circular, floral-structured UWB antenna integrated with multiband wireless applications operating from 4-18 GHz with a dimension of 30×30 mm 2 . In [16], a compact (16×22 mm 2 ) flower-slotted UWB antenna integrated with the Ku band for DBS and FSS applications is described, covering an impedance bandwidth of 3.45-18.45 GHz with WLAN, and the downlink of X-bands is notched by a via and L-shaped parasitic elements, respectively. A compact (20×20 mm 2 ) eplison-structured UWB antenna is reported to cover 10.4-30 GHz bandwidth with a peak efficiency of 90.8% and a fractional bandwidth (FBW) of 97% is reported [17].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of printed-circuit UWB antenna designs are reported in the 3-10 GHz span, with very few designs persisting to cover higher frequencies such as the 3-30 GHz band, with promising applications in medical, air-bone intercept, radar, missile systems, and short-range tracking systems. The Ku band (12)(13)(14)(15)(16)(17)(18) is used for high resolution tracking and tracking the satellite within the bandwidths of approximately 12.87-14.43 GHz and the vehicular radar band (22)(23)(24)(25)(26)(27)(28)(29) [12]. As wireless system tools develop and use higher frequency ranges to provide higher data transfer, a UWB antenna with a frequency range far beyond the FCC-authorized band is required to monitor and enforce various standard compliances, such as EIRP, immunity tests, and interferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation